A Great Sign Appeared in the Sky . Audience-Oriented Criticism of Revelation 12:1-6 - Blajer, Piotr (The Biblical Annals, 2022)
Revelation 12:1-6 recounts two signs that appear in heaven. The first sign is a woman and the second one is a dragon with seven heads, ten horns and seven diadems on its seven heads. The somewhat unusual description of the two signs has its grand finale in 12:4-6 which tells about the interaction between the woman and the dragon, as well as her child. The dragon, aware that its power must last for only a short period, a symbolic ten days, tries to swallow the child to whom the woman is about to give birth. In this way, the dragon wants to thwart and frustrate God’s plan. The newborn child is caught up by God to his throne in heaven. The reference to the OT helps the audience to identify the newborn child as the Messiah who will shepherd all the nations. The presentation of the child’s mission to shepherd all the nations assures the audience that God’s plan will be realized. This vision assures the audience that God is almighty, and that he is the ‘hidden actor’ in the entire vision. The reader-oriented exegesis of the passage discloses how the audience respond to the author’s rhetorical arguments and presentation.